Discussion on Key Technology of High-speed Maglev Railway Bridge Structures in Low Vacuum Tube - Daliang ZHAO; Shubin LIU; Bing WANG (机车电传动)
As a new type of transportation system, the vacuum tube high-speed traffic has become a research hotspot and a key development direction in the world. The vacuum tube pressure, blockage ratio, aerodynamic drag, maglev system, vehicle body, etc. were mainly studied by domestic and foreign scholars at present. So combined with the medium and low speed maglev transit, high-speed maglev transportation design specification and design philosophy, the main problems such as tube structure, material, temperature load and fatigue load of the bridge structure in low vacuum tube high-speed maglev railway were preliminarily discussed .